Emaranhamentos religiosos: Debates contemporâneos na América Latina e na África do Oeste: Religious entanglements: Contemporary debates in Latin America and West Africa - Oliveira, Rosenilton Silva de; Labañino, Yumei de Isabel Morales (Revista Desenvolvimento Social, 2024)
A founding theme of the Human Sciences, studies on religious phenomena are fundamental to understanding the logic of social organization, power relations, the production of hierarchies and classifications of belonging, the constitution of identities and cultural heritage. In addition to analyses that deal with liturgies, cosmologies and institutional organization, research that places the religious field in dialogue with other spheres of social life is also relevant. This dossier is part of this debate by highlighting research that has investigated contemporary religious phenomena and their interfaces in Latin America and West Africa.